Nanostructure based on self-assembly and cross-linking method, electrode thereof, and preparation method thereof

CN116553472BActive Publication Date: 2026-10-23INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210097820.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-27
Publication Date
2026-10-23
Estimated Expiration
2042-01-27

AI Technical Summary

Technical Problem

但断裂结技术、光刻技术、电化学沉积等技术的制备方式不仅步骤繁琐,也难于进行精确的控制

Benefits of technology

[0060]1、基于极尖的纳米间隙电极的器件具有实现用于计算和生物传感的潜在能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116553472B_ABST
    Figure CN116553472B_ABST
Patent Text Reader

Abstract

The application provides a nanostructure based on self-assembly and cross-linking method, an electrode thereof and a preparation method. 6 The nanostructure has super-high conductivity, and the conductivity can reach 10 6 S / m. Further, by performing ion beam focused cutting on the nanostructure, a nano-gap electrode with a width less than 20 nm and very sharp is prepared. The nanostructure containing graphene nanowire and the nano-gap electrode with high conductivity have good application prospects in molecular-level devices for computing and biosensing. Since the gap is very suitable for detecting nanoscale molecules, different performance of nanoscale biomolecules can be detected by constructing molecular circuits and molecular devices. The sensor with single virus detection capability, reusability, low cost, portability and compatibility with smart phones can help the society to get rid of current and future pandemics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterials synthesis and application, specifically relating to a nanostructure based on self-assembly and cross-linking, its electrodes, and preparation method. Background Technology

[0002] With the rapid development of semiconductor technology, the size of integrated circuits has continued to shrink, reaching the limits of miniaturization technology. This has led to an increasing demand for devices formed at the molecular scale. Molecular-based devices offer advantages in electronic applications, including low cost, low power consumption, and unique optical and electrical properties. Molecular-scale devices have found widespread application in biosensors. To achieve the detection of nanoscale biomaterials, the biosensor component needs to possess excellent durability and stability, adaptability to various testing environments, and the characteristics of miniaturization, modularity, and interfacing. Carbon nanoelectrodes, with their excellent conductivity, sharp structure, and sufficiently small gaps, can immobilize nanoscale biomolecules, enabling their effective application in biosensing.

[0003] Because of the extremely small size of the gaps between electrodes, nano-gap structures have high research value. However, the fabrication methods of techniques such as fracture junction technology, photolithography, and electrochemical deposition are not only cumbersome but also difficult to control precisely. Summary of the Invention

[0004] Therefore, the purpose of this invention is to overcome the deficiencies in the prior art and provide a preparation method based on self-assembly, cross-linking, immobilization with metal, and subsequent high-temperature annealing to obtain a conductivity as high as 10. 6 High conductivity nanostructures containing nanowires with a conductivity of S / m were developed, along with high-performance, extremely sharp nanogap electrodes fabricated using these nanostructures. Devices based on these extremely sharp nanogap electrodes have the potential to realize computational and biosensing applications. Since the gap is well-suited for the detection of nanoscale molecules, the detection of nanoscale biomolecules with varying performance can be achieved by constructing molecular circuits and devices. Robust, self-cleaning, and reusable carbon nanoelectrodes can be applied in biosensors through electrophoresis or similar single-virus immobilization mechanisms. Sensors with single-virus detection capabilities, reusability, low cost, portability, and smartphone compatibility have the potential to help society overcome current and future pandemics.

[0005] Before describing the content of this invention, the following terms are defined as follows:

[0006] The term "PDMS" refers to polydimethylsiloxane.

[0007] The term "DBA-COOH" refers to anthracene bromide carboxylic acid.

[0008] To achieve the above objectives, a first aspect of the present invention provides a nanostructure based on self-assembly and cross-linking, the nanostructure comprising: a substrate, a two-dimensional material transferred onto the substrate, a conductive long-chain cross-linked nanostructure, and a metal electrode; wherein,

[0009] The conductive long-chain cross-linked nanostructure includes nanowires;

[0010] Preferably, the nanowires are graphene nanowires;

[0011] Preferably, the width of the nanowire is 30–600 nm, more preferably 40–300 nm;

[0012] Preferably, the length of the nanowire is 3–20 μm, more preferably 7–10 μm; and / or

[0013] Preferably, different parts of the same nanowire have different widths.

[0014] According to the first aspect of the present invention, a nanostructure based on self-assembly and cross-linking is provided, wherein the substrate is selected from one or more of the following: mica, diamond, silicon wafer, silicon dioxide, with mica being the most preferred.

[0015] The two-dimensional material is selected from one or more of the following: graphene, boron nitride, metal sulfides, metal selenides, with boron nitride being the most preferred; and / or

[0016] The metal electrode is selected from one or more of the following: gold, silver, copper, and titanium, with gold being the most preferred.

[0017] A second aspect of the present invention provides a nanogap electrode, which is fabricated by the nanostructure based on self-assembly and cross-linking method described in the first aspect;

[0018] Preferably, the nanogap electrode has a very sharp shape; and / or

[0019] Preferably, the minimum gap of the nano-gap electrode is less than 30 nm, more preferably less than 25 nm, and most preferably less than 20 nm.

[0020] A third aspect of the present invention provides a method for preparing the nanostructures based on self-assembly and cross-linking as described in the first aspect, the method comprising the following steps:

[0021] (1) Transfer two-dimensional materials onto a substrate and grow precursor molecules onto the surface of the two-dimensional material / substrate;

[0022] (2) This causes the precursor monomer molecules in step (1) to cross-link with each other, forming a long-chain cross-linked nanostructure;

[0023] (3) Deposit metal electrodes onto the long-chain cross-linked nanostructure prepared in step (2) to solidify the nanostructure;

[0024] (4) The nanostructure solidified in step (3) is obtained by high-temperature annealing;

[0025] Preferably, step (1) further includes the following steps: growing a two-dimensional material on a copper foil, attaching PDMS to one side of the two-dimensional material, immersing and etching the copper foil, retrieving the two-dimensional material / PDMS using a substrate, and baking and evaporating to obtain the two-dimensional material / substrate; and / or

[0026] Preferably, in step (3), the metal electrodes are connected by nanowires, and / or the distance between the metal electrodes is 1 to 10 μm, more preferably 3 to 8 μm, and even more preferably 4 to 7 μm.

[0027] According to a third aspect of the method of the present invention, step (1) further includes the following step: the precursor molecules are grown onto a substrate in a vacuum cavity by epitaxial growth; wherein,

[0028] The precursor molecule is a polycyclic aromatic hydrocarbon, preferably a polycyclic aromatic hydrocarbon with a functional group capable of supramolecular interaction with two-dimensional materials on one side of the molecule in the horizontal direction and halogen atoms on both sides in the vertical direction; the functional group is preferably selected from one or more of the following: carboxyl, aldehyde, cyano, more preferably carboxyl or aldehyde, and most preferably carboxyl.

[0029] Preferably, the sublimation temperature of the epitaxial growth is 130–180°C, more preferably 150–170°C, and most preferably 160°C;

[0030] Preferably, the epitaxial growth time is 10–60 min, more preferably 10–40 min, and most preferably 30 min; and / or

[0031] Preferably, the environmental pressure for epitaxial growth is 1×10⁻⁶. -10 mbar~1×10 -8 mbar, further preferably 1×10 -10 mbar.

[0032] According to the method of the third aspect of the present invention, in step (2), the cross-linking between the precursor monomer molecules is completed in a vacuum cavity by irradiation by a radiation source;

[0033] Preferably, the wavelength of the radiation source is less than 350 nm, and most preferably less than 300 nm;

[0034] Preferably, when the radiation source is ultraviolet light, the power is greater than 250W, more preferably greater than 300W; the irradiation time is greater than 10 hours, more preferably greater than 12 hours; and / or

[0035] Preferably, the ambient pressure of the radiation source is 1×10⁻⁶. -10 mbar~1×10 -8 mbar, further preferably 1×10 -10 mbar.

[0036] According to the method of the third aspect of the present invention, wherein step (4) further includes the following steps: bombarding the substrate with an electron beam emitted by a DC power supply, and annealing the nanostructure solidified in step (3) at high temperature, so that the carbon-carbon single bonds in the polymer are converted into carbon-carbon double bonds, forming a nanostructure containing nanowires with high electrical conductivity.

[0037] Preferably, the high-temperature annealing temperature needs to reach 1000℃ and be maintained for 8 to 12 minutes, most preferably 10 minutes;

[0038] Preferably, the heating rate of the high-temperature annealing process needs to be maintained at 1-5°C / s, more preferably 1-4°C / s, and even more preferably 2-3°C / s; and / or

[0039] Preferably, the ambient pressure during the high-temperature annealing is 1×10⁻⁶. -10 mbar~1×10 -8 mbar, further preferably 1×10 -10 mbar.

[0040] A fourth aspect of the present invention provides a method for preparing the nano-gap electrode described in the second aspect, the method comprising:

[0041] (A). A nanostructure containing nanowires prepared according to the method described in the third aspect;

[0042] (B) The nanostructure containing nanowires prepared in step (A) is subjected to ion beam cutting to form the extremely sharp nano gap electrode;

[0043] Preferably, the ion source for the ion beam cutting is gallium ions;

[0044] Preferably, the voltage for ion beam cutting is 10.0–50.0 keV, more preferably 20.0–40.0 keV, and most preferably 30.0 keV; and / or

[0045] Preferably, the current for ion beam cutting is 0.5 to 5 pA, more preferably 0.5 to 2 pA, and most preferably 1.1 pA.

[0046] A fifth aspect of the present invention provides a molecular device circuit, the molecular device circuit comprising the nanogap electrode described in the second aspect or the nanogap electrode prepared according to the method described in the fourth aspect.

[0047] A sixth aspect of the present invention provides a nanoscale biomolecule detection device, the detection device comprising the nano gap electrode described in the first aspect or the nano gap electrode prepared according to the method described in the fourth aspect or the molecular device circuit described in the fifth aspect;

[0048] The nanoscale biomolecule detection device is preferably a biosensor, and / or

[0049] The samples detected by the nanoscale biomolecule detection device are preferably selected from one or more of the following: cells, viruses, nanowires, nanoribbons, nanotransistors, polymers, metal particles, and smoke particles.

[0050] More preferably, the virus detection is a single virus detection.

[0051] According to a specific embodiment of the present invention, the method for preparing a high-conductivity nanostructure containing graphene nanowires includes:

[0052] Two-dimensional materials / substrates are prepared by transfer method;

[0053] Molecules are grown on two-dimensional materials / substrates;

[0054] The radiation method is used to induce cross-linking of molecules;

[0055] Metal electrodes are vapor-deposited onto the cross-linked graphene nanostructure to solidify the nanostructure.

[0056] High-temperature annealing enables molecules to form a nanostructure containing graphene nanowires with high electrical conductivity.

[0057] According to another specific embodiment of the present invention, the extremely sharp nanogap electrode prepared based on the nanostructure containing graphene nanowires is prepared by the following method: the nanostructure containing graphene nanowires is ion-beam cut to form an extremely sharp nanogap electrode.

[0058] The nano-gap electrode prepared by the method of this invention has potential applications in the following areas: ① quantum computing; ② applications in molecular device circuits; ③ detection of nanoscale biomolecules, such as cells and viruses; ④ sensors for materials such as nanowires, nanotubes, and polymers. Figure 5 This demonstrates some potential applications of this nano-gap electrode.

[0059] The nanostructures and nano-gap electrodes based on self-assembly and cross-linking methods of the present invention may have, but are not limited to, the following beneficial effects:

[0060] 1. Devices based on extremely sharp nano-gap electrodes have the potential to realize computing and biosensing applications.

[0061] 2. Because this gap is highly suitable for the detection of nanoscale molecules, molecular circuits and devices can be constructed to detect nanoscale biomolecules with varying properties. Through electrophoresis or similar single-virus immobilization mechanisms, robust, self-cleaning, and reusable carbon nanoelectrodes can be applied in the field of biosensors. Sensors with single-virus detection capabilities, reusability, low cost, portability, and smartphone compatibility have the potential to help society overcome current and future pandemics.

[0062] 3. The preparation method of the present invention is simple and easy to control precisely.

[0063] 4. The nanostructure containing nanowires prepared by the method of this invention has a conductivity as high as 10. 6 S / m.

[0064] 5. The preparation method of this invention is applicable to materials of different sizes, such as polymers, nanoribbons and nanotubes of different widths, and cells, which can be cut according to their size. It can not only prepare nano-gap electrodes with very narrow gaps, but also nano-gap electrodes of different widths depending on the material or molecule used. Attached Figure Description

[0065] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings, wherein:

[0066] Figure 1 The flowcharts for the preparation of a high-conductivity nanostructure containing graphene nanowires in Example 1 and the preparation of a nano-gap electrode in Example 2 are shown.

[0067] Figure 2 A schematic diagram of the nanostructure based on self-assembly and cross-linking prepared in Example 1 of the present invention is shown. The nanostructure has a width of 30-600 nm and a length of 3-20 μm.

[0068] Figure 3 A schematic diagram of the structure of the nano-gap electrode prepared in Example 2 of the present invention is shown, with a width of 20-30 nm.

[0069] Figure 4The diagram illustrates the processes for preparing a high-conductivity nanostructure containing graphene nanowires in Example 1 and a nano-gap electrode in Example 2. In the diagram, ① represents the precursor forming a continuous molecular structure through π-π stacking and subsequent interlayer and layer-by-layer growth; ② represents cross-linking of molecules through irradiation; ③ represents the formation of a metal electrode by vapor deposition, immobilizing the cross-linked nanostructure; ④ represents high-temperature annealing to form the high-conductivity nanostructure containing graphene nanowires; and ⑤ represents the formation of a sharp nano-gap electrode structure through focused ion beam cutting.

[0070] Figure 5 Scanning electron microscope (SEM) images and atomic force microscope (AFM) images of the high-conductivity graphene nanostructure prepared in Example 1 of this invention are shown. Figure 5 a shows that different parts of the same nanowire have different widths under a scanning electron microscope; Figure 5 bd shows different types of nanowires under an atomic force microscope, among which Figure 5 b shows a nanowire bundle formed by binding multiple nanowires together. Figure 5 c shows nanowires with low crystallinity. Figure 5 d shows highly crystallized nanowires.

[0071] Figure 6 A scanning electron microscope image of the extremely sharp nanogap electrode prepared in Example 2 of the present invention is shown, wherein... Figure 6 a and Figure 6 b represents images of the nanowires before and after focused ion beam cutting, respectively.

[0072] Figure 7 Nano-gap electrodes with different nano-gap widths, fabricated from nanowires of varying widths, are shown. Figure 7 AC demonstrated that nanowires with widths ranging from 50 to 300 nm can be cut into nano-gap electrodes with a spacing of 20-30 nm. Figure 7 a demonstrates an extremely sharp nano-gap electrode with a width of less than 20 nm. Figure 7 AC demonstrated that 20-30 nm nano-gap electrodes can be obtained on nanowires with widths of 40 nm, 80 nm and 300 nm respectively. Figure 7 Figure d shows a 150 nm wide nano-gap electrode prepared without using the method of this invention.

[0073] Figure 8 A schematic diagram illustrates the application of the fabricated extremely sharp nanogap electrode as a sensor for detecting different molecules or materials, in which... Figure 8 'a' represents the novel coronavirus. Figure 8 b represents DNA. Figure 8c represents nanowires or transistors. Figure 8 d represents smoke particle molecules. Detailed Implementation

[0074] The present invention will be further illustrated below with specific embodiments. However, it should be understood that these embodiments are merely for more detailed and specific illustration and should not be construed as limiting the present invention in any way.

[0075] This section provides a general description of the materials and testing methods used in the experiments of this invention. While many of the materials and methods of operation used to achieve the objectives of this invention are well known in the art, the invention is still described in as much detail as possible herein. It will be apparent to those skilled in the art that, unless otherwise stated in the context, the materials and methods of operation used in this invention are well known in the art.

[0076] The reagents and instruments used in the following examples are as follows:

[0077] Material:

[0078] Mica, purchased from Changchun Taiyuan Company.

[0079] PDMS and boron nitride grown on copper foil were both purchased from Graphene Supermarket.

[0080] Dibromoanthracene was purchased from Alpha Reagent Co., Ltd.

[0081] Reagents:

[0082] Ammonium persulfate solution was purchased from Beijing Tongguang Reagent Co., Ltd.

[0083] instrument:

[0084] The ultraviolet light source was purchased from Osram, model HWL.

[0085] The electron beam evaporation system was purchased from Taiwan Fulim Technology, model FU-12PEB.

[0086] The focused ion beam system was purchased from FEI Corporation, USA, model Helios 600i.

[0087] The low-temperature four-probe electrical platform was purchased from Janis, USA, model Keithley 4200SCS.

[0088] The ultra-high resolution field emission scanning electron microscope (UPES) was purchased from Hitachi, Japan, model Regulus 8230.

[0089] The scanning tunneling microscope, purchased from Veco in the United States, is a Brucker Multimode 8.

[0090] Example 1

[0091] This embodiment illustrates the preparation method of nanostructures based on self-assembly and cross-linking of the present invention.

[0092] Figure 1 The flowcharts for the preparation of a high-conductivity nanostructure containing graphene nanowires in Example 1 and the preparation of a nano-gap electrode in Example 2 are shown. Figure 2 A schematic diagram of the nanostructure based on self-assembly and cross-linking method prepared in Example 1 of the present invention is shown. Figure 4 The diagram illustrates the processes for preparing a high-conductivity nanostructure containing graphene nanowires in Example 1 and a nano-gap electrode in Example 2. In the diagram, ① represents the precursor forming a continuous molecular structure through π-π stacking and subsequent interlayer and layer-by-layer growth; ② represents cross-linking of molecules through irradiation; ③ represents the formation of a metal electrode by vapor deposition, immobilizing the cross-linked nanostructure; ④ represents high-temperature annealing to form the high-conductivity nanostructure containing graphene nanowires; and ⑤ represents the formation of a sharp nano-gap electrode structure through focused ion beam cutting.

[0093] The preparation method includes the following steps, as illustrated in the diagram below. Figure 4 As shown:

[0094] Step (1): The selected two-dimensional material is transferred to the selected substrate via a transfer method. The two-dimensional material must be an insulator with high-temperature resistance. This includes, but is not limited to, graphene, boron nitride, metal sulfides, and metal selenides. The substrate should be a material with sufficient hardness, high-temperature resistance, and insulation properties to meet the requirements of subsequent fabrication processes. The materials used in this embodiment are as follows: boron nitride is used as the two-dimensional material, and mica is used as the substrate. Specifically, boron nitride grown on copper foil is used, and PDMS is attached to one side of the boron nitride surface, ensuring full contact. Then, the substrate is immersed in a 0.1 mol / L ammonium persulfate solution for 6 hours. The copper foil reacts with the ammonium persulfate solution and is etched. After copper etching, only the PDMS / boron nitride structure remains. Subsequently, the boron nitride / PDMS in the ammonium persulfate solution is retrieved using a mica sheet and baked at 80°C for 2 hours to evaporate the residual solution, thus obtaining the boron nitride transferred to the mica substrate.

[0095] Step (2): The precursor molecule is grown onto the substrate surface in a vacuum chamber. The selected molecular precursor must meet the following requirements: it belongs to polycyclic aromatic hydrocarbons (PAHs), and one side of the molecule in the horizontal direction has a functional group capable of supramolecular interaction with two-dimensional materials, such as carboxyl, aldehyde, or cyano groups, and both sides in the vertical direction have halogen atoms. In this embodiment, DBA-COOH is used. This molecule has a terphenyl structure and a carboxyl group on one side of the molecule in the horizontal direction. This molecule is grown onto the substrate in a vacuum chamber via epitaxial growth using an organic evaporation source. The required sublimation temperature is 160°C, the time is 30 minutes, and the ambient pressure is 1×10⁻⁶. -9 mbar. During growth, due to the hydrophilic interaction between the carboxyl group side of the precursor molecule and the boron nitride substrate, and the hydrophobic interaction between the biphenyl group side and the boron nitride substrate, the molecule tends to combine with the substrate with the carboxyl group structure facing downwards and the biphenyl group structure facing upwards, and continuously forms an ordered stacked structure.

[0096] Step (3): The monomer molecules are bonded together by irradiation with a radiation source within a vacuum chamber. This step requires that the molecules have halogen atoms or other molecules with cross-linking capabilities on both sides adjacent to other molecules. In this embodiment, anthracene carboxylic acid bromide (DBA-COOH) is used. The synthesis process of this molecule is as follows: anthracene bromide is mixed with tetrahydrofuran (THF) and methanol to form a solution, bromine gas is introduced, and recrystallization is performed to obtain anthracene carboxylic acid bromide (DBA-COOH). After undergoing a supramolecular reaction with boron nitride on the substrate, this molecule will form an ordered orientation, and its molecules will be connected with bromine atoms in the parallel direction. The wavelength of the radiation source selected for irradiation needs to be lower than 300 nm, and the vacuum degree needs to be 10. -9 The radiation source is irradiated at the mbar level. In this embodiment, the radiation source is ultraviolet light, with a power greater than 300W, and the irradiation time needs to be more than 12 hours. Because ultraviolet photons have short wavelengths and high energy, they can break the chemical bonds between carbon and halogen atoms, causing the halogen atoms to sublimate and detach from the substrate surface. Due to the detachment of halogen atoms, the carbon atoms have extra unpaired electrons, which form covalent bonds with adjacent carbon atoms, thereby forming a long-chain cross-linked nanostructure from the monomer.

[0097] Step (4): The nanostructure is solidified by evaporating metal electrodes onto the substrate where the cross-linked nanostructure is formed. The mask should be used so that the distance between the electrodes deposited on it is only a few micrometers to ensure that there are nanowires connecting the electrodes. Figure 3A TEM grid is used as a mask, with a grid width of 36 micrometers and a distance of 6 micrometers between grids. This means the electrode size deposited using this mask is 36 micrometers, and the distance between electrodes is 6 micrometers. Gold is used as the metal electrode in this embodiment. Since some of the cross-linked nanostructures sublimate during the high-temperature annealing process in step (5), the pre-deposited electrodes can fix the cross-linked nanostructures, stabilizing their structure and facilitating their transformation into graphene nanowire structures.

[0098] Step (5): Carbon-carbon single bonds are converted into carbon-carbon double bonds by high-temperature annealing in a vacuum chamber. Since the cross-linked nanostructure formed by the monomer in the previous step still does not have good conductivity, it cannot be used in nano-gap electrodes and needs to be further processed. The substrate is bombarded with an electron beam emitted by a DC power supply to perform high-temperature annealing. At this time, the carbon-carbon single bonds in the polymer are gradually converted into carbon-carbon double bonds, thereby forming the high-conductivity nanostructure containing graphene nanowires. The length is on the micrometer level and the width is on the hundred-nanometer level. The length and width of the same nanowire are different. In this embodiment, DBA-COOH is used as the molecule and needs to be annealed in a vacuum of 10. -9 High-temperature annealing is performed at the mbar level. The high-temperature annealing needs to reach 1000℃, and the heating rate needs to be maintained at 2-3 degrees Celsius per second, and the temperature needs to be maintained at 1000℃ for 10 minutes.

[0099] Figure 5 Scanning electron microscope (SEM) images and atomic force microscope (AFM) images of the high-conductivity graphene nanostructure prepared in Example 1 of this invention are shown. Figure 5 a shows that different parts of the same nanowire have different widths under a scanning electron microscope; Figure 5 bd shows different types of nanowires under an atomic force microscope, among which Figure 5 b shows a nanowire bundle formed by binding multiple nanowires together. Figure 5 c shows nanowires with low crystallinity. Figure 5 d shows highly crystallized nanowires.

[0100] Example 2

[0101] This embodiment illustrates the method for preparing the extremely sharp nano-gap electrode of the present invention.

[0102] Figure 1 The flowcharts for the preparation of a high-conductivity nanostructure containing graphene nanowires in Example 1 and the preparation of a nano-gap electrode in Example 2 are shown. Figure 3 A schematic diagram of the structure of the nano-gap electrode prepared in Example 2 of the present invention is shown. Figure 4The diagram illustrates the processes for preparing a high-conductivity nanostructure containing graphene nanowires in Example 1 and a nano-gap electrode in Example 2. Based on the high-conductivity nanostructure containing graphene nanowires prepared in Example 1, a highly pointed nano-gap electrode structure is formed by focused ion beam cutting in step ⑤.

[0103] Based on the high-conductivity graphene nanowire-containing nanostructure prepared in Example 1, the graphene nanowires were cleaved on a substrate with deposited electrodes using a focused ion beam. Gallium ions were used as the ion source, with a voltage of 30.0 keV and a current of 1.1 pA. After a single cleavage by the focused ion beam, nano-gap electrodes with a sharpest gap of less than 20 nm were obtained. Atomic force microscopy images before and after cleavage are shown below. Figure 6 As shown, scanning electron microscope images of nanowires of different widths and nano-gap electrodes of different widths are as follows. Figure 7 As shown.

[0104] Figure 6 A scanning electron microscope image of the extremely sharp nanogap electrode prepared in Example 2 of the present invention is shown, wherein... Figure 6 a and Figure 6 b represents images of the nanowires before and after focused ion beam cutting, respectively.

[0105] Figure 7 Nano-gap electrodes with different nano-gap widths, fabricated from nanowires of varying widths, are shown. Figure 7 AC demonstrated that nanowires with widths ranging from 50 to 300 nm can be cut into nano-gap electrodes with a spacing of 20-30 nm. Figure 7 a demonstrates an extremely sharp nano-gap electrode with a width of less than 20 nm. Figure 7 AC demonstrated that 20-30 nm nano-gap electrodes can be obtained on nanowires with widths of 40 nm, 80 nm and 300 nm respectively. Figure 7 Figure d shows a 150 nm wide nano-gap electrode prepared without using the method of this invention.

[0106] As shown in the figure above, the extremely sharp nanogap electrode prepared by this invention has a gap of 20nm-30nm and is very sharp. Compared with other nanogap electrodes with larger widths, such as... Figure 7 The nano-gap electrode shown in d has a gap of 150 nm. Due to the small gap, the extremely sharp nano-gap electrode of the present invention can detect a larger current value when the detected particle passes between the electrodes, thus having higher sensitivity compared to electrodes with larger gaps.

[0107] Example 3

[0108] This embodiment is used to illustrate the conductivity of the nanostructure based on self-assembly and cross-linking obtained by Example 1.

[0109] Using a four-probe electrical testing platform (model Keithley 4200SCS), the IV curve between the electrodes was tested, and the conductivity was calculated using the formula: σ=L / RS (where R is the resistance obtained from the IV curve, L is the width between the electrodes, and S is the cross-sectional area).

[0110] Testing showed that the conductivity between the graphene nanowire electrodes prepared in Example 1 could reach 10. 6 S / m.

[0111] Example 4

[0112] This embodiment illustrates the application of the nano-gap electrode prepared by Example 2.

[0113] The nano-gap electrode prepared in Example 2, when applied to a sensor, such as... Figure 8 As shown.

[0114] Figure 8 A schematic diagram illustrates the application of the fabricated extremely sharp nanogap electrode as a sensor for detecting different molecules or materials, in which... Figure 8 'a' represents the novel coronavirus. Figure 8 b represents DNA. Figure 8 c represents nanowires or transistors. Figure 8 d represents smoke particle molecules.

[0115] This invention provides a method for fabricating extremely sharp nanogap electrodes, applicable to various sizes, such as polymers, nanoribbons and nanotubes of different widths, and cells, all of which can be cut according to their size. Not only can very narrow gap nanogap electrodes be fabricated, but nanogap electrodes of different widths can also be fabricated depending on the material or molecule used.

[0116] Although the invention has been described to a certain extent, it is apparent that appropriate variations can be made to the various conditions without departing from the spirit and scope of the invention. It is understood that the invention is not limited to the described embodiments, but falls within the scope of the claims, which include equivalent substitutions for each of the elements.

Claims

1. A method for preparing nanostructures based on self-assembly and cross-linking, characterized in that, The nanostructures prepared based on self-assembly and cross-linking methods include: a substrate, a two-dimensional material transferred onto the substrate, a conductive long-chain cross-linked nanostructure, and a metal electrode; wherein the conductive long-chain cross-linked nanostructure includes nanowires; the nanowires are graphene nanowires; the width of the nanowires is 30~600nm; the length of the nanowires is 3~20μm; different parts of the same nanowire have different widths; Furthermore, the method includes the following steps: (1) The two-dimensional material is transferred to the substrate, and the precursor molecules are grown on the surface of the two-dimensional material / substrate. The two-dimensional material is grown on a copper foil, and PDMS is attached to one side of the two-dimensional material. After immersion etching of the copper foil, the two-dimensional material / PDMS is retrieved with the substrate and baked and evaporated to obtain the two-dimensional material / substrate. The precursor molecules are grown on the substrate in a vacuum chamber by epitaxial growth. The precursor molecules are polycyclic aromatic hydrocarbons with a functional group on one side of the molecular horizontal direction that can interact with the two-dimensional material supramolecularly, and halogen atoms on both sides of the vertical direction. The functional group is selected from one or more of the following: carboxyl, aldehyde, cyano. The sublimation temperature of the epitaxial growth is 130~180℃, the epitaxial growth time is 10~60min, and the environmental pressure of the epitaxial growth is 1×10 -10 mbar ~1×10 -8 mbar; (2) This causes the precursor monomer molecules in step (1) to cross-link with each other, forming a long-chain cross-linked nanostructure; (3) Metal electrodes are vapor-deposited onto the long-chain cross-linked nanostructure prepared in step (2) to solidify the nanostructure. The metal electrodes are connected by nanowires, and the distance between the metal electrodes is 1~10μm. (4) By high-temperature annealing the nanostructure cured in step (3), a nanostructure containing nanowires with high electrical conductivity is obtained.

2. The method according to claim 1, characterized in that, In the nanostructure: The substrate is selected from one or more of the following: mica, diamond, silicon wafer, and silicon dioxide; The two-dimensional material is selected from one or more of the following: graphene, boron nitride, metal sulfides, and metal selenides; The metal electrode is selected from one or more of the following: gold, silver, copper, titanium; and / or The width of the nanowire is 40~300nm.

3. The method according to claim 2, characterized in that, In the nanostructure: The substrate is mica; The two-dimensional material is boron nitride; and / or The metal electrode is gold.

4. The method according to claim 1, characterized in that, In step (3), the distance between the metal electrodes is 3~8μm.

5. The method according to claim 4, characterized in that, In step (3), the distance between the metal electrodes is 4~7μm.

6. The method according to claim 1, characterized in that, In step (1): The functional group is a carboxyl group or an aldehyde group; The sublimation temperature of the epitaxial growth is 150~170℃; The epitaxial growth time is 10-40 min; and / or The environmental pressure for the epitaxial growth is 1×10⁻⁶. -10 mbar.

7. The method according to claim 6, characterized in that, In step (1): The functional group is a carboxyl group; The sublimation temperature of the epitaxial growth is 160°C; and / or The epitaxial growth time is 30 minutes.

8. The method according to claim 1, characterized in that, In step (2), the cross-linking between the precursor monomer molecules is completed in a vacuum chamber by irradiation with a radiation source.

9. The method according to claim 8, characterized in that, In step (2): The wavelength of the radiation source is less than 350 nm; When the radiation source is ultraviolet light, the power is greater than 250W; the irradiation time is greater than 10 hours; and / or The ambient pressure irradiated by the radiation source is 1×10⁻⁶. -10 mbar ~1×10 -8 mbar.

10. The method according to claim 9, characterized in that, In step (2): The wavelength of the radiation source is less than 300 nm; When the radiation source is ultraviolet light, the power is greater than 300W; the irradiation time is greater than 12h; and / or The ambient pressure irradiated by the radiation source is 1×10⁻⁶. -10 mbar.

11. The method according to claim 1, characterized in that, The step (4) further includes the following steps: bombarding the substrate with an electron beam emitted by a DC power supply, and annealing the nanostructure solidified in step (3) at high temperature, so that the carbon-carbon single bonds in the polymer are converted into carbon-carbon double bonds, forming a nanostructure containing nanowires with high electrical conductivity.

12. The method according to claim 11, characterized in that, In step (4): The high-temperature annealing temperature needs to reach 1000℃ and be maintained for 8~12 minutes; The heating rate of the high-temperature annealing process needs to be maintained at 1~5℃ / s; and / or The ambient pressure for the high-temperature annealing is 1×10⁻⁶. -10 mbar ~1×10 -8 mbar.

13. The method according to claim 12, characterized in that, In step (4): The high-temperature annealing temperature needs to reach 1000℃ and be maintained for 10 minutes; The heating rate of the high-temperature annealing process needs to be maintained at 1~4℃ / s; and / or The ambient pressure for the high-temperature annealing is 1×10⁻⁶. -10 mbar.

14. The method according to claim 13, characterized in that, In step (4), the heating rate of the high-temperature annealing process needs to be maintained at 2~3℃ / S.

15. A nano-gap electrode, characterized in that, The nanogap electrode is prepared by a nanostructure prepared by any one of claims 1-14.

16. The nano-gap electrode according to claim 15, characterized in that: The nano-gap electrode has a very sharp shape; and / or The minimum gap of the nano-gap electrode is less than 30 nm.

17. The nano-gap electrode according to claim 16, characterized in that: The minimum gap of the nano-gap electrode is less than 25 nm.

18. The nano-gap electrode according to claim 17, characterized in that: The minimum gap of the nano-gap electrode is less than 20 nm.

19. A method for preparing a nano-gap electrode as described in any one of claims 15-18, characterized in that, The method includes: (A) The method according to any one of claims 1 to 14 is used to prepare nanostructures comprising nanowires; (B) The nanostructure containing nanowires prepared in step (A) is ion-beam cut to form an extremely sharp nano-gap electrode.

20. The method according to claim 19, characterized in that: The ion source for the ion beam cutting is gallium ions; The voltage for ion beam cutting is 10.0~50.0 keV; and / or The current for ion beam cutting is 0.5~5 pA.

21. The method according to claim 20, characterized in that: The voltage for ion beam cutting is 20.0~40.0 keV; and / or The current for ion beam cutting is 0.5~2 pA.

22. The method according to claim 21, characterized in that: The voltage for ion beam cutting is 30.0 keV; and / or The current for the ion beam cutting is 1.1 pA.

23. A molecular device circuit, characterized in that, The molecular device circuit includes a nano-gap electrode as described in any one of claims 15-18.

24. A nanoscale biomolecule detection device, characterized in that, The detection device includes a nano gap electrode as described in any one of claims 15-18 or a molecular device circuit as described in claim 23.

25. The nanoscale biomolecule detection device according to claim 24, characterized in that: The nanoscale biomolecule detection device is a biosensor, and / or The samples detected by the nanoscale biomolecule detection device are selected from one or more of the following: cells, viruses, nanowires, nanoribbons, nanotransistors, polymers, metal particles, and smoke particles.

26. The nanoscale biomolecule detection device according to claim 25, characterized in that, When the nanoscale biomolecule detection device is a virus detection device, the virus detection is a single virus detection.

Citation Information

Patent Citations

  • Field effect transistor and preparation method and application thereof

    CN111463289A

  • Flexible transparent electrode with high conductive coverage rate and preparation method thereof

    CN112614627A

  • Shape-altered graphene nanobridge array, transfer-aligned for biomolecular sensing and information storage

    WO2021237182A1